Xiaoxuming Decoction: A Traditional Herbal Recipe for Stroke With Emerging Therapeutic Mechanisms - Qian Zhang; Qian Zhang; Yue Wang; Aiwen Chen; Aiwen Chen; Xinwei Huang; Xinwei Huang; Qianyu Dong; Qianyu Dong; Zhen Li; Zhen Li; Xiaofei Gao; et al. (Frontiers Media S.A., 2021)
Xiaoxuming decoction (XXMD) has been traditionally used to manage stroke though debates on its clinical efficacy were present in the history. Till nowadays, it is still one of the most commonly used herbal recipes for stroke. One of the reasons is that a decent proportion of ischemic stroke patients still have residue symptoms even after thrombolysis with rt-PA or endovascular thrombectomy. Numerous clinical studies have shown that XXMD is an effective alternative therapy not only at the acute stage, but also at the chronic sequelae stage of ischemic stroke. Modern techniques have isolated groups of compounds from XXMD which have shown therapeutic effects, such as dilating blood vessels, inhibiting thrombosis, suppressing oxidative stress, attenuating nitric oxide induced damage, protecting the blood brain barrier and the neurovascular unit. However, which of the active compounds is responsible for its therapeutic effects is still unknown. Emerging studies have screened and tested these active compounds aiming to find individual compounds that can be used as drugs to treat stroke. The present study summarized both clinical evidence of XXMD in managing stroke and experimental evidence on its molecular mechanisms that have been reported recently using advanced techniques. A new perspective has also been discussed with an aim to provide new targets that can be used for screening active compounds from XXMD.